The impact of corporate governance and firm performance on waste and effluent disclosure: Evidence from polluting industries in Indonesia - Nirwana, Jehan Tasya; Wedari, Linda Kusumaning (International Journal of Management and Sustainability, 2023)
This study examined the influence of corporate governance – including the presence of board gender diversity, board independence, board attention, and audit committee – and firm performance on waste and effluent disclosure in polluting industry companies in Indonesia. This study used secondary data obtained from the companies’ annual and sustainability reports during the period 2017 to 2021. The waste and effluent disclosure was measured using a scoring method based on Global Reporting Initiative (GRI) Standard 306: Waste and Effluent. This study focused on companies in five polluting industries, including Pulp and Paper, Chemicals, Oil and Gas, Metals and Mining, and Infrastructure, Utilities, and Transportation, listed on the Indonesia Stock Exchange. The results of the study show that corporate governance, including the presence of board gender diversity, board independence, board attention, and audit committee, has a significant influence on waste and effluent disclosure. In contrast, firm performance, which was proxied by return on assets (ROA), has no significant influence on the waste and effluent disclosure of companies in polluting industries listed on the Indonesia Stock Exchange.